Defining and Characterizing Open Peer Review: A Review of the Literature - Ford, Emily (Journal of Scholarly Publishing, 2013)
Changes in scholarly publishing have resulted in a move toward openness. To this end, new, open models of peer review are emerging. While the scholarly literature has examined and discussed open peer review, no established definition of it exists, nor are there uniform implementations of open peer review processes. This article examines the literature discussing open peer review, identifies common open peer review definitions, and describes eight common characteristics of open peer review: signed review, disclosed review, editor-mediated review, transparent review, crowd-sourced review, pre-publication review, synchronous review, and post-publication review. This article further discusses benefits and challenges to the scholarly publishing community posed by open peer review and concludes that open peer review can and should exist within the current scholarly publishing paradigm.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDQtNC0wMDE